2014
DOI: 10.1002/2014ja019885
|View full text |Cite
|
Sign up to set email alerts
|

A solar cycle of upper thermosphere density observations from the EISCAT Svalbard Radar

Abstract: We exploit a recently developed technique, based on ion-neutral coupling, which allows estimations of the upper thermospheric neutral density using measurements of ionospheric plasma parameters made by the European Incoherent Scatter (EISCAT) Svalbard Radar (ESR). The technique is applied to a 13 year long data set of measurements for the purpose of studying and quantifying the effect of solar activity on the upper thermospheric density inside the polar cap. We concentrate on the effect of solar activity at 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…ESR hmF2 was estimated for each profile in a way similar to Vickers et al (2014). Cubic spline interpolation was used to set a fixed distance of 10 km between each point in the profile.…”
Section: Methodsmentioning
confidence: 99%
“…ESR hmF2 was estimated for each profile in a way similar to Vickers et al (2014). Cubic spline interpolation was used to set a fixed distance of 10 km between each point in the profile.…”
Section: Methodsmentioning
confidence: 99%
“…In situ comparisons with the CHAMP satellite show good agreement. Vickers et al (2014) used this technique on the EIS-CAT Svalbard radar for the period 2000 to 2013 and showed that F10.7 solar irradiance is a very good proxy for thermospheric density variations with only a small seasonal dependence. In addition, the long-term trend of declining thermospheric density was observed.…”
Section: Upper Thermospherementioning
confidence: 99%
“…Neutral particle densities in the thermosphere, at the altitude of the F ‐region peak, are approximately 10 14 m −3 . At high latitudes, there is an approximately linear correlation between density of atomic oxygen, a major constituent of the neutral atmosphere at this altitude, and F 10.7 solar flux illumination (Vickers et al, ). Variations in thermosphere are strongly dependent on both solar illumination and activity.…”
Section: Introductionmentioning
confidence: 99%